CALIDAD DE ATENCIÓN AL CLIENTE EN LA CORPORACIÓN NACIONAL DE TELECOMUNICACIONES EP-AGENCIA BABAHOYO - Pinela Guisado, Edinson Medardo (2018)
oday, customers value more to receive a good service than to buy cheap, customers neither forget nor forgive a company that has failed to meet their expectations, which has eroded the customer's average loyalty. Companies must be firmly anchored in the commercial vanguard and adapt to various factors such as social and technological changes that directly influence the quality of customer service. The CNT-EP is a macro Ecuadorian entity, with national agencies, which are dedicated to providing telecommunications services; the service delivery activity generates or implies developing a good customer care service; The permanence of the companies in the markets necessarily depends on the strategies and managerial decisions focused on various purposes that include the good treatment of the subscriber and the quality of customer service.